2019
DOI: 10.3389/fnhum.2019.00220
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Consumer Ethnocentrism and Cultural Familiarity on Brand Preference: Evidence of Event-Related Potential (ERP)

Abstract: The tendency of customers’ preference to their local brands over the foreign ones is known as consumer ethnocentrism, and it is an important issue in international marketing. This study aims at identifying the behavioral and neural correlates of Consumer Ethnocentrism in the field of brand preference, using event-related potential (ERP). We sampled subjects from two ethnic groups, a Chinese ethnic group and a sub-Saharan Black African group from Zhejiang University. The subjects faced two sequential stimuli, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…The surrounding environment, including friendship and emotion, can affect product endorsement and willingness-to-pay (Liao et al, 2019). Consumer behavior, financial services, evaluation stage, and decision-making in advertising are related to neural cortex response changes in current researches, further to verify a feasibility application in neuromarketing (Senior et al, 2015;Ramsøy et al, 2018;Wei et al, 2018;Ceravolo et al, 2019;Ma et al, 2019;Hu et al, 2020). Vences et al (2020) summarized a theoretical review of the main neural scientific research on neuromarketing's effectiveness, which is a neural measure tool, to enhance the emotional connection between consumers and organizations in social networks.…”
Section: Introductionmentioning
confidence: 90%
“…The surrounding environment, including friendship and emotion, can affect product endorsement and willingness-to-pay (Liao et al, 2019). Consumer behavior, financial services, evaluation stage, and decision-making in advertising are related to neural cortex response changes in current researches, further to verify a feasibility application in neuromarketing (Senior et al, 2015;Ramsøy et al, 2018;Wei et al, 2018;Ceravolo et al, 2019;Ma et al, 2019;Hu et al, 2020). Vences et al (2020) summarized a theoretical review of the main neural scientific research on neuromarketing's effectiveness, which is a neural measure tool, to enhance the emotional connection between consumers and organizations in social networks.…”
Section: Introductionmentioning
confidence: 90%
“…Ma, et al (Ma et al, 2019) The influence of the consumer ethnocentrism and cultural familiarity on brand preference: Evidence of event-related potential…”
Section: Alcoholic Beveragesmentioning
confidence: 99%
“…The results of He and Lu's study [59] showed that consumer ethnocentrism can exist during the evaluation and selection of brands matched to ethnic groups as well as the origin of the product (local vs. imported); the in-group recommended logos were treated more favorably than the out-group recommended logos by the higher ethnocentrism group. The results of the study by Ma Q, Abdeljelil, and Hu [60] demonstrated that in addition to the origin of the product (local vs. imported), consumer ethnocentrism can also exist during the evaluation and selection of brands appropriate to ethnic groups.…”
Section: Literature Reviewmentioning
confidence: 99%